Pengaruh Kinerja Keuangan Terhadap Pendapatan Saham Dengan DPR Sebagai Variabe Moderasi di BEI - Devi, Ari Cintya; Sudjarni, Luh Komang (E-Jurnal Manajemen; Vol 1 No 1 (2012), 2012)
The research was done because there was an inconsistence of the result found about the impact of finance performance to the stock return. This inconsistence of result encourage the used of moderator  variable  that expected gave impact to the relevance between independent variables and dependent variables, that is dividen payout ratio. This research was done in 6 Real Estate and Property company in Indonesian Stock Exchange by year 2006-2010. The F-test result showed that simultantly the finance performance were giving a significant impact . The T-test shows Current ratio and Debt to Equity Ratio were giving a negative and significant impact to the stock returns, but partially Return on Assetss and Price Earning Ratio did not give any impact to the stock returns. After the residual test was done, dividend payout ratio was not able to reinforce the relation between financial performance and stock returns.